Effect of Different Solvents on Toxicity and Secondary Metabolites of Mangkokan Leaves (Polyscias scutellaria (Burm.f.) Fosberg) by Brine Shrimp Lethality Test (BSLT) Method - Syam, Akhirul Kahfi; Sabilia, Syahra Asfi; Riyanti, Soraya (Pharmacon: Jurnal Farmasi Indonesia, 2024)
Mangkokan (Polyscias scutellaria (Burm.f.) Fosberg) is one of the plants belonging to the Araliaceae family. Empirically, mangkokan plants, especially the leaves, are used by the community as traditionalmedicine. Mangkokan leaves need to be developed into a source of natural materials such as biopesticides, biolarvicide, and anticancer agents because they have toxic compounds. Secondary metabolite compounds of mangkokan leaves consist of flavonoids, saponins, monoterpenes-sesquiterpenes, and steroids. This study aims to determine the toxicity of n-hexane, ethyl acetate, and ethanol extracts of mangkokan leaves using the Brine Shrimp Lethality Test (BSLT) method. Mangkokan leaves were extracted by graded maceration method using n-hexane, ethyl acetate, and 96% ethanol solvents. All three extracts were tested BSLT on Artemia salina larva test animals. The toxicity level is expressed by the LC50 value obtained from the probit analysis. The LC50 value of n-hexane, ethyl acetate, and ethanol extracts was 146.724 μg/mL, respectively; 66.029 μg/mL; and 92.007 μg/mL. The results showed that all three extracts were toxic.